Modul Herediter Noether dan Prima (HNP) Dari Modul Sederhana Chen A_` - Risnawita; Savoji, Fatemeh; Dwi Devi Wulandari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Let K be a field and is line graph with infinite path. Let L is a Leavitt path algebra with correspondence with graph E. Suppose is a module over ring (written- module , a module is considered to be hereditary if all its submodules are projective. A module is called a Noetherian module if is a finitely generated module. Suppose M is a left module over the gelanggang (written - module ). A proper submodule of is said to be prime if with and implies or . In this paper we will look at the characteristics of the hereditary nooetherian and prime modules in the context of Leavitt path algebra. Let L is a Leavitt path algebra, where E is a line graphs with infinite path and M is a module over Leavitt path algebra L, we find that then M is simple modules which is hereditary noetherian and not prime modules. Misalkan adalah suatu lapangan dan merupakan graf garis yang lintasannya tak terhingga. Misalkan adalah aljabar lintasan Leavitt yang berkorespondensi dengan graf Misalkan adalah modul di atas gelanggang (ditulis -modul ), modul dikatakan herediter jika semua submodulnya bersifat proyektif. Modul M disebut modul Noetherian jika adalah modul yang dibangun secara hingga. Misalkan adalah modul kiri atas gelanggang (ditulis -modul ). Suatu submodul sejati dari dikatakan prima jika dengan dan mengakibatkan atau . Dalam tulisan ini kita akan melihat karakteristik modul herediter noether dan prima dalam konteks aljabar lintasan Leavitt. Misalkan adalah aljabar lintasan Leavitt, dengan adalah graf garis yang memuat lintasan tak berhingga. Dan adalah modul atas aljabar lintasan Leavitt kita temukan bahwa M adalah modul sederhana yang merupakan modul herediter Noether dan bukan modul prima.